Minimizing information asymmetry interference using optimal channel assignment strategy in wireless mesh networks - Rahman, Gohar; Chai, Chuah Wen; Shah, Sadiq; Daud, Misbah (The Science and Information (SAI) Organization Limited, 2019)
Multi-radio multi-channel wireless mesh networks (MRMC-WMNs) in recent years are considered as the prioritized choice for users due to its low cost and reliability. MRMCWMNs is recently been deployed widely across the world but still these kinds of networks face interference problems among WMN links. One of the well-known interference issue is information asymmetry (IA). In case of information asymmetry interference the source mesh nodes of different mesh links cannot sense each other before transmitting data on the same frequency channel. This non-coordination leads to data collision and packet loss of data flow and hence degrades the network capacity. To maximize the MRMC-WMN capacity and minimize IA interference, various schemes for optimal channel assignment have been proposed already. In this research a novel and near-optimal channel assignment model called Information Asymmetry Minimization (IAM) model is proposed based on integer linear programming. The proposed IAM model optimally assigns orthogonal or non-overlapping channels from IEEE 802.11b technology to various MRMC-WMN links. Through extensive simulations we show that our proposed model gives 28.31% network aggregate network capacity improvement over the existing channel assignment model.